Longitudinal CSF proteomics identifies NPTX2 as a prognostic biomarker of Alzheimer's disease. Issue 12 (13th May 2021) - Libiger, Ondrej; Shaw, Leslie M.; Watson, Mark H.; Nairn, Angus C.; Umaña, Kelly L.; Biarnes, Michael C.; Canet‐Avilés, Rosa M.; Jack, Clifford R.; Breton, Yannick‐André; Cortes, Laetitia; Chelsky, Daniel; Spellman, Daniel S.; et al.
Abstract: Introduction: Biomarkers that reflect pathologic processes affecting neuronal function during preclinical and early stages of Alzheimer's disease (AD) are needed to aid drug development. Methods: A targeted, stable isotope, quantitative mass spectrometry‐based investigation of longitudinal changes in concentrations of previously identified candidate biomarkers was performed in cerebrospinal fluid (CSF) of Alzheimer's Disease Neuroimaging Initiative participants who were classified as cognitively normal (CN; n  = 76) or with mild cognitive impairment (MCI; n  = 111) at baseline. Results: Of the candidate biomarkers, the CSF concentration of neuronal pentraxin 2 (NPTX2), a protein involved in synaptic function, exhibited rates of change that were significantly different between three comparison groups (i.e., CN vs. MCI participants; AD pathology positive vs. negative defined by phosphorylated tau181/amyloid beta1‐42 ratio; and clinical progressors vs. non‐progressors). The rate of change of NPTX2 also significantly correlated with declining cognition. Discussion: CSF NPTX2 concentration is a strong prognostic biomarker candidate of accelerated cognitive decline with potential use as a therapeutic target.